Designing different functional frameworks from 0D to 3D for exploring structural correlation with photocatalytic activity. (5th September 2017) - Li, Huijun; He, Yaling; Zhao, Wenling; Li, Qingqing; Xu, Zhouqing; Wang, Yuan
Graphical abstract: Three different structural complexes have been constructed by parasol-based ligands and different metal ions for exploring structural correlation with photocatalytic activity. Abstract: The main theme of interest is to design functional metal–organic frameworks (MOFs) for exploring structural correlation with photocatalytic activity. So firstly, three different structural MOFs, namely, Cd(APAPT)2 I2 ·2H2 O (1 )( APAPT = 3-(5-Amino-1H-pyrazol-4-yl)-5-(3-amino-1H-pyrazol-4-yl)-3, 5-dihydro-[1, 2, 4]triazol-4-ylamine), [Mn(APAPT)(SO4 )(H2 O)] n (2 ) and{[Zn3 (APAPT)2 (SO4 )(OH)2 ]·(H2 O)} n (3 ) constructed by the same parasol-based ligands and different metal ions are reported here. Complex1 shows one-dimensional chain linked by mononuclear Cd units through π⋯π interactions. Complex2 possesses two-dimensional layer with left- and right-handed helical chains. Complex3 with infinite Zn-cluster chains is a three-dimensional porous framework. The structural diversity indicates that the APAPT with different coordination modes play important roles in tuning the dimensionalities and structures of the title complexes. Photocatalytic studies show that the MB degradation rates were 63.2%, 51.3% and 80.3% for complexes1 –3, respectively. The results manifest that the more extended networks may aid in the transport of excited holes/electrons to the surface to initiate the photocatalytic decomposition reaction with MB. Besides, steric hindrance etc. helical chains or weaving structure may lead to a relative lower photocatalytic activity.